Handbook for transversely finned tube heat exchanger design - Pis'mennyi, Eugene; Polupan, Georgiy; Carvajal-Mariscal, Ignacio; Sanchez-Silva, Florencio; Pioro, I. L. (Igor Leonardovich) (Academic Press is an imprint of Elsevier, 2016)
Based on extensive experimental studies and tested at leading design and research institutions, this book provides an extensive set of materials for calculating and designing convective surfaces from transversely finned tubes, with a particular emphasis on power plant applications. --